Implications of Service Quality and Waiting Time on Patient Satisfaction Through Employee Communication at Perwira Community Health Center, Bekasi City - Ramadhan, Andhito; Zaharuddin, Zaharuddin; Junaedi, Dudun Junaedi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the challenges faced by Puskesmas Perwira Kota Bekasi as a primary healthcare provider in maintaining service quality, where service quality, waiting time, and employee communication are key factors influencing patient satisfaction. The research aims to analyze the implications of service quality and waiting time on patient satisfaction through employee communication at Puskesmas Perwira. Given that efficient and quality healthcare services strongly affect patient perceptions and satisfaction, this study used a quantitative approach with a survey of 100 patients who had received services at the health center. Data were analyzed using path analysis to test direct and indirect effects of independent variables on patient satisfaction, with employee communication as a mediating variable. The findings show that service quality and waiting time significantly influence patient satisfaction, both directly and indirectly, through employee communication. Effective communication by employees is a vital factor in reinforcing the impact of service quality and waiting efficiency. These results provide important implications for Puskesmas management in improving public healthcare services.